Evaluation of electronic pheromone trap capture conditions for Ips sexdentatus with climatic and temporal factors - Özcan, Gonca Ece; Tabak, Hakan Şükrü (Springer Science and Business Media LLC, 2021)
Controlling forest pests to maintain the sustainability of forests and ecosystem balance is one of the interests of modern forestry. In the evaluation of damage risks associated with forest pests, pheromone traps attract attention by providing early warnings. With the development of these traps in line with modern technology, more reliable data are obtained; these data are important in the identification and planning of pest management. In this study, a pheromone trap with electronic control unit was tested under field conditions. The capture of adult Ips sexdentatus under natural conditions during 103 days of the flying period was evaluated; 97.2% of the beetles captured in the trap were the target species. The comparison of the number of beetles recorded by the trap and manual counts revealed that the trap worked with an error margin of approximately 4%. However, no statistically significant difference was noted between these two counting methods. During the study, 59% of the total beetles were captured between May 27 and June 25. The average temperature at the period of the capture was 20.09 °C, average humidity was 66%, and average wind speed was 2.9 m/s. Of the captures, 73.9% occurred in the temperature range of 15-24.9 °C, 61.1% occurred in humidity range of 61-90%, 89.6% occurred at a wind speed of 0.3-5.4 m/s, and 77.3% occurred within the period from sunrise to sunset. When these four parameters were evaluated together, the most strongly associated parameter was daylight, followed by temperature, wind speed, and humidity.
Keywords: Coleoptera; Animals; Weevils; Electronics; Insect Control; Ecosystem; Pheromones; Environmental Monitoring; 15. Life on land